Developing and validating an instrument for the assessment of tourism carrying capacity in Pulau Perhentian marine park - Nasir, Nadia; Ibrahim, Mansor (Global Academic Excellence, 2019)
Carrying capacity is one of the concepts in tourism management and planning. Though it shows a remarkable solution in controlling the impacts of tourism towards the environment, it involves a very complex process and vagueness in indicating attributes and criteria to govern this framework. This study is carried out to evaluate the relevant indicators for the tourism carrying capacity in Pulau Perhentian marine park. In this paper, a conceptual model based on a study from the current literature was proposed. Data collected from the questionnaire was analyzed to validate and test the reliability of the instruments. The findings of this paper will be used for developing the model in the future